2017
DOI: 10.1177/1971400916689371
|View full text |Cite
|
Sign up to set email alerts
|

Systemic metastases from central nervous system ependymoma: case report and review of the literature

Abstract: Ependymal tumours in adults are rare, accounting for less than 4% of primary tumours of the central nervous system, and exceptionally metastasise outside the nervous system. In this study, we present a case of anaplastic ependymoma, which developed metastases outside the nervous system less than a year after its clinical onset. A healthy 65-year-old woman suddenly presented with drowsiness of unknown origin, accompanied by ingravescent fatigue, inability to maintain the upright posture, headache, nausea and vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…Anaplastic ependymomas are classified as WHO Grade III neoplasms and are considered clinically more aggressive with a higher risk of recurrence and drop metastasis. [1] Clinically, the present case was different from that reported by Reni et al [2] where more rapid signs and symptoms were found owing to the relatively aggressive nature of the tumor. In terms of the radiological findings, owing to the relatively progressive characteristics, these tumors may show predilection for parenchymal involvement as well as focal dural thickness with enhancement (“dural tail” sign).…”
contrasting
confidence: 92%
See 1 more Smart Citation
“…Anaplastic ependymomas are classified as WHO Grade III neoplasms and are considered clinically more aggressive with a higher risk of recurrence and drop metastasis. [1] Clinically, the present case was different from that reported by Reni et al [2] where more rapid signs and symptoms were found owing to the relatively aggressive nature of the tumor. In terms of the radiological findings, owing to the relatively progressive characteristics, these tumors may show predilection for parenchymal involvement as well as focal dural thickness with enhancement (“dural tail” sign).…”
contrasting
confidence: 92%
“…Most lesions showed heterogeneous enhancement. These lesions account for 8% to 33% [1] of all lesions and are particularly detected in infratentorial lesions. Therefore, imaging protocols, including intra-cranial and spinal MRI examinations, are essential pre-operatively.…”
mentioning
confidence: 99%
“…As mentioned previously, SM from MPBT is extremely rare, and their image characteristics are much the same as those from extracranial malignant tumors. [15,16,[19][20][21][22][23] Their similar image feature supports our nine SM patients being representative of all "true-metastasis" when comparing to IESL from MPBT. Further study comparing IESL and SM from MPBT may be considered.…”
Section: Discussionsupporting
confidence: 66%
“…Magnetic resonance imaging (MRI) is an accurate diagnostic tool with a primary indication in several condition both for a diagnostic and interventional intent (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Notably, MRI has been established as dominant modality use in neuroradiological field due to its excellent soft tissue contrast (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), which allowed an accurate evaluation of intracranial structures. This characteristic proves to be particularly advantageous in the study of pituitary gland; MRI, indeed, provide a detailed depiction of the pituitary anatomy and its relationship with adjacent structures, helping from the detection of micro alteration of its architecture to the formulation of an adequate treatment planning.…”
Section: Introductionmentioning
confidence: 99%